Hallucinatory Activity In Schizophrenia : The Relationship With Childhood Memories, Submissive Behavior, Social Comparison, And Depression - Carvalho, Célia (2017)
ICAP 2015: 17th International Conference on Applied Psychology. Tokyo, Japan, May 28-29, 2015.